Biosensor based on Cellulose Acetate/Glutaraldehyde Membrane Electrodes for detection of organophosphorus pesticides - Mashuni Mashuni; Fitri Handayani Hamid; M Jahiding; Andi Muhammad Naufal Khaeri (Jurnal Kimia Sains dan Aplikasi, 2023)
In recent years, sensor applications have been critical in many fields, especially food safety and pesticides. Organophosphorus pesticides (OPPs) can be detected using a potentiometric biosensor with a membrane electrode made of a new natural material based on cellulose acetate (CA). Acetylcholinesterase was immobilized to 15% modified CA membrane electrodes using glutaraldehyde (GTA) as crosslinking agent and gold (Au) electrode. An indirect method used an acetylthiocholine chloride (ATCl) substrate to find OPPs like chlorpyrifos, profenophos, and diazinon. The working electrode was an CA/GTA membrane electrode, and the reference electrode was an Ag/AgCl electrode, whose potential value was measured with a potentiometer. The surface morphology of the biosensor membrane was investigated using scanning electron microscopy with energy-dispersive X-ray spectroscopy (SEM/EDX). It showed that the CA membrane has a smooth, porous surface and is very dense, and its structure consists of 71.27% carbon (C) and 28.73% oxygen (O) with an average diameter of 562.33 nm. A potentiometric biosensor based on AChE inhibition for the detection of OPPs showed a limit of detection (LoD) of 1×10−6 μg/L with a linearity range of 1×10−6–1.0 μg/L. The %inhibition value for the chlorpyrifos pesticide was 14.44 to 73.08%, profenophos was 11.98 to 77.98%, and diazinon was 18.58 to 83.27%. Therefore, higher inhibitor concentrations (OPPs) have a greater ability to prevent the AChE enzyme from breaking down the acetylcholine substrate. The biosensor with the CA membrane has a wide linearity range and a low detection limit. The potentiometer rapidly detects pesticide residues.